2010
DOI: 10.1371/journal.pone.0011799
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Signature of Rapid IHHNV (Infectious Hypodermal and Hematopoietic Necrosis Virus) Expansion in Wild Penaeus Shrimp Populations

Abstract: Infectious hypodermal and hematopoietic necrosis virus (IHHNV) is a widely distributed single-stranded DNA parvovirus that has been responsible for major losses in wild and farmed penaeid shrimp populations on the northwestern Pacific coast of Mexico since the early 1990's. IHHNV has been considered a slow-evolving, stable virus because shrimp populations in this region have recovered to pre-epizootic levels, and limited nucleotide variation has been found in a small number of IHHNV isolates studied from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
1
28
2
2
Order By: Relevance
“…We surmise this to be the possible reason for the high sequence divergence of these two isolates from the Hawaiian isolate. In contrast to the report of Tang and Lightner [79], there was an unexpectedly high mean rate of nucleotide substitution (1.39 9 10 -4 substitutions/site/year) was reported by Robles-Sikisaka et al [70] who compared sequences of the IHHNV capsid protein from 89 penaeid shrimp, along with 14 sequences isolated from P. stylirostris and P. monodon from different geographic locations. These studies indicate that IHHNV haplotype and nucleotide diversity is higher than previously reported and the genetic diversity is not uniform across geographic regions.…”
Section: Genotype Variationcontrasting
confidence: 56%
See 1 more Smart Citation
“…We surmise this to be the possible reason for the high sequence divergence of these two isolates from the Hawaiian isolate. In contrast to the report of Tang and Lightner [79], there was an unexpectedly high mean rate of nucleotide substitution (1.39 9 10 -4 substitutions/site/year) was reported by Robles-Sikisaka et al [70] who compared sequences of the IHHNV capsid protein from 89 penaeid shrimp, along with 14 sequences isolated from P. stylirostris and P. monodon from different geographic locations. These studies indicate that IHHNV haplotype and nucleotide diversity is higher than previously reported and the genetic diversity is not uniform across geographic regions.…”
Section: Genotype Variationcontrasting
confidence: 56%
“…Despite the fact that wild type IHHNV was circulating in 1990 [63], [Krabsetsve and Owens unpublished] and again in 2008 [71], the inserted virus-related sequence is *15 % divergent from the wild-type virus, suggesting an ancient exposure to a IHHNV-like virus. If the DNA mutation rates found by Robles-Sikisaka et al [70] hold for Australian IHHNV-like sequences, then the Australian IHHNV-like strain that produced the integrated sequences last shared a common ancestor with IHHNV *4.3 million years ago. Furthermore, a 950 bp IHHNV-like sequence incorporating all of NS2 and most of NS1 has been found in freshwater crayfish Cherax quadricarinatus which has 70 % identity to Australian virus-like sequence [Rusaini and Owens unpublished].…”
Section: Normal Cellmentioning
confidence: 92%
“…However, signals of positive selection were discovered in several IHHNV lineages, in which the rates of amino acid replacements exceeded those of synonymous substitutions when compared to neutral expectations for genetic drift and mutation (Robles-Sikisaka et al, 2010). As with recombination, this mechanism has not been addressed extensively in IHHNV.…”
Section: Positive Selectionmentioning
confidence: 99%
“…(Tattersall et al, 2005). A decade later, the wild P. stylirostris fishery recovered, and subsequent surveys of wild populations of P. stylirostris from the Gulf of California revealed that the virus is well established in the natural population with prevalence reaching as high as 100% (Morales-Covarrubias et al, 1999;Robles-Sikisaka, Bohonak, McClenaghan, & Dhar, 2010). Subsequently, the disease was found in Penaeus vannamei where it did not cause mortalities but instead deformities referred to as runt deformity syndrome (RDS) (Bell & Lightner, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, esto no debe justificar su presencia en post larvas de importación, porque el IHNNV presenta una alta tasa evolutiva y una amplia diversidad genética en las cepas aisladas (Robles et al 2010), existiendo el riesgo latente de aparición de cepas más virulentas, que pueden poner en peligro a los cultivos de L. vannamei y las poblaciones silvestres de L. stylirostriss, especie para la cual el IHHNV es mortal.…”
Section: Discussionunclassified